Educational Technology Integration in Mathematics Education: Challenges and Opportunities for Enhancing Achievement at Junior Secondary School Level in Sri Lanka - Sithara Jayamali Liyanage Nanayakkara Godewasam Liyanage (Postgraduate Program, University of Mataram, 2025)
Abstract—This study aimed to investigate the current state of educational technology integration in junior secondary science and mathematics education in Sri Lanka’s Galle Division, focusing on challenges, opportunities, and strategies for improving student achievement. A mixed-methods approach was employed, combining structured questionnaires, open-ended interviews, and classroom observations. Data were collected from 70 students (Grades 6–9) and 16 mathematics teachers. The instruments included Likert-scale items, open-response questions, and observation checklists to assess perceptions, practices, and integration of educational technology. The results revealed limited use of educational technologies, with only 11% of students reporting smartboard use and 17% computer access. While 92% of students preferred technology-enhanced learning, 37% reported disinterest in mathematics. Teachers showed strong agreement on benefits (82–94%) but low implementation confidence (13%). A misconception prevailed, with both teachers and students perceiving technology mainly as physical tools rather than pedagogical approaches. This study highlights how educational technology is narrowly understood in developing contexts and underscores the importance of reframing it as a pedagogical approach rather than limited tools. By applying the TPACK framework, the study advances knowledge on bridging awareness, confidence, and practice gaps in mathematics education.